Health Education in Management Radiological Examination in the Era of the Covid 19 Pandemic - Cucu Herawati; Yusron Adi Utomo; Iin Kristanti; Supriatin Supriatin; Nuniek Tri Wahyuni (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The Covid-19 pandemic impacts increasing psychological problems (anxiety disorders, depression, and insomnia) in the community and health workers. People experience clinical anxiety, so they are afraid to check their health to health services when they experience symptoms of illness. The purpose of this community service is to increase the knowledge and attitudes of health workers in providing good health education to the community so that people understand health behaviour and can make decisions based on the information that has been obtained. This education was conducted online for 300 health workers (Indonesian Radiographers/PARI), with the media zoom meeting. The implementation of this education begins with a pre-test, implementation of education, questions and answers, then a post-test. The results of the pre-test before the implementation of health education obtained a mean value of 36.50, a median of 30, and a standard deviation of 17,060, while the post-test results after the implementation of health education obtained a mean value of 93.00, a median of 100, and a standard deviation of 10.773. There is an increase in the knowledge of health education participants between before and after the health education is given. Recommendations from this community service activity are expected that health workers can continue to provide good health education to the community. The level of anxiety and stigma against Covid-19 decreases, and people feel calm and safe to check their health.